Study on continuing vocational training for rural activities - Ana Ursu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The study aims to analyze the modalities of vocational training in rural areas in order to identify systematic contents that are relevant to define the perception of the general role of continuing vocational training in the economic and social development of rural areas, the functions of continuing vocational training in the complex process of transformation of the agri-food economy, and the position of vocational training in Romania. For the study, the qualitative analysis method was used to establish the terms of the concept of continuing vocational training, to identify other researches that have investigated continuing vocational training of adults, to identify priority areas of analysis for capturing training needs for rural activities. The results highlight that lifelong learning should be addressed as an objective need, especially in the field of agriculture, leading to increased labour productivity, reduced vulnerability and not necessarily job creation.
Keywords: I20; I25; J20; J24; J43; O52; Q10; R10; 330; vocational training; agriculture; productivity; skills; occupational standard